Communication—Surprisingly High Fast Charge Volumetric Capacities of Hard Carbon Electrodes in Sodium-Ion Batteries. Issue 11 (18th November 2021) - Rudola, Ashish; Wright, Christopher J.; Barker, Jerry
Abstract : We show herein that electrode-level effects of commercially-available hard carbon (HC) material, as a function of the HC loading, can have two surprising positive outcomes in sodium-ion (Na-ion) pouch cells. First, a HC electrode's plating-free volumetric capacity actually increases as its loading (and areal capacity) decreases, and secondly, the plating-free volumetric capacity at sub-30 min charging times for HC as Na-ion anode, can be better vs that of graphite anode in lithium-ion (Li-ion) cells at the electrode-level, and actually be significantly higher than the latter at sub-20 min and sub-15 min charging times, despite HC's lower density than graphite.